La autoestima y su influencia en el rendimiento académico de los estudiantes de 9no. año de educación básica de la unidad educativa cyber school en el periodo lectivo 2015-2016 - Coronel Flores, Karen Vanessa (2015)
Self-esteem in adolescents is considered an essential mechanism or engine to achieve the proposed goals no matter how difficult they may be to achieve. Self-esteem is formed even with the thoughts, experiences and feelings we have of itself, can be positive or negative. Therefore it is considered a fundamental variable in the lives of people, but also in the stage of adolescence, as it directly influences the formation; and is responsible for the successes and failures in education……